1997
DOI: 10.1007/s11665-997-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on the machinability of resulfurized composite free-cutting steels

Abstract: The machinability of S, S-Ca, S-RE, and S-RE-Ca system resulfurized composite free-cutting steels were investigated, where RE is rare earths, mostly cerium. The experimental results showed that in the low cutting speed range (_<35 m/min), the S-RE system free-cutting steel had better machinability than the others and that the S-RE-Ca system free-cutting steel exhibited the best machinability at high cutting speeds. A protective layer capable of preventing diffusion wear was formed on the rake face ofa P30 tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…[5][6][7][8] Manganese sulfide inclusions are typical inclusions detected in non-quenched and tempered (NQT) steels. Medium content of sulfur is usually added into steels for their beneficial effects on improving machinability, 9,10) retarding grain growth 11,12) and inducing intragranular ferrite. 11,13,14) However, the large-sized elongated MnS inclusions, which exist in longitudinal section after deformation, are severely detrimental to the transverse mechanical properties of steels.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Manganese sulfide inclusions are typical inclusions detected in non-quenched and tempered (NQT) steels. Medium content of sulfur is usually added into steels for their beneficial effects on improving machinability, 9,10) retarding grain growth 11,12) and inducing intragranular ferrite. 11,13,14) However, the large-sized elongated MnS inclusions, which exist in longitudinal section after deformation, are severely detrimental to the transverse mechanical properties of steels.…”
Section: Introductionmentioning
confidence: 99%
“…The works of Averin [7], Lou [8], and Jiang et al [9] have shown that Ca can partially transform MnS into CaS, and they can form a solid solution with each other to generate a new phase of (Mn,Ca)S. The hardness of (Mn,Ca)S is relatively high and the ductility is relatively low, and thus it can improve the transverse impact…”
Section: Modification Mechanism and Route Of Ca On Sulfidesmentioning
confidence: 99%
“…The works of Averin [7], Lou [8], and Jiang et al [9] have shown that Ca can partially transform MnS into CaS, and they can form a solid solution with each other to generate a new phase of (Mn,Ca)S. The hardness of (Mn,Ca)S is relatively high and the ductility is relatively low, and thus it can improve the transverse impact toughness of the steel after rolling. Carl [10] studied the effects of Ca treatment on inclusions in steel, and found that some of the Ca in steel combines with Al2O3 and forms liquid calcium-aluminate, which can be the nucleation core of (Mn,Ca)S inclusions in the subsequent solidification process.…”
Section: Modification Mechanism and Route Of Ca On Sulfidesmentioning
confidence: 99%
“…Nowadays, the non-quenched and tempered steel has been widely applied to manufacturing fields, particularly in the form of the machining parts. So a good machinability which is mainly affected by the distribution, composition and quantity of the inclusions in steel is quite vital [1][2][3]. However, the machinability of non-quenched and tempered steel improved is mainly to modify the inclusions by adding elements to liquid steel during the refining process [4,5].…”
Section: Introductionmentioning
confidence: 99%